Histomorphological evaluation of teat of Sahiwal and Holstein Friesian cattle during lactation and non-lactation stage - CHAUHAN, ANSHU ANARJIT; BANSAL, BALJINDER KUMAR; BANSAL, NEELAM (The Indian Journal of Animal Sciences, 2024)
The present study was conducted on the teat of Sahiwal and Holstein Friesian (HF) cattle during lactating and non-lactating periods. The samples were collected in 10% NBF, processed to obtain paraffin sections, and stained with various stains. The results revealed that teat skin in Sahiwal and HF cows were reported to be thicker at the teat tip, followed by the mid part and minimum at the base of the teat. The epidermal pegs were pointed and elongated in non-lactating, whereas blunt and flattened in lactating animals. There was stretching of different layers of skin in the lactating animals due to flattened epidermal pegs and dermal papillae. The lining epithelium of teat cistern varied from stratified cuboidal to columnar type and showed mucosal foldings, which were comparatively less in Sahiwal than in HF. The annular folds were well developed in Sahiwal cattle. The lactiferous glands were smaller and lined by low cuboidal epithelium in Sahiwal cows, whereas their number and size were more in the HF. The folds in Furstenberg’s rosette varied from 10-14 in Sahiwal and 6-10 in HF cattle. The teat canal epithelium’s thickness was higher in HF than in Sahiwal cows. Teat muscle sphincter contained smooth muscle fibres, blood vessels, nerves, and collagen, reticular and elastic fibres. The amount of collagen fibres were relatively more in Sahiwal cattle. It may be concluded that the chances of intramammary infection are comparatively less in Sahiwal cattle as compared to HF ones due to anatomical variations in the formation of annular folds, Furstenberg’s rosette and teat sphincter.